Memetic Computing - Lim, Meng-Hiot.; Ong, Yew-Soon.; Gustafson, Steven; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Memetic Computing features articles on high quality research in hybrid metaheuristics (including evolutionary hybrids) for optimization, control and design in continuous and discrete optimization domains. It goes beyond current search methodologies towards innovative research on the emergence of cultural artifacts such as game, trade and negotiation strategies and, more generally, rules of behavior as they apply to, for example, robotic, multi-agent and artificial life systems. Memetic Computing is an avenue for the latest results in natural computation, artificial intelligence, machine learning, operational research and natural sciences, which are combined in novel ways so as to transcend the intrinsic limitations of a single discipline. Potential authors are invited to submit original research articles for publication consideration at any time. Reviews and short research communications are also welcomed. Further information on submission, format, lengths and style files is available through the journal website. All manuscripts should be submitted electronically using the Online Submission system. We aim to achieve a typical turnaround time of not more than 3 months for the review process. Some (but not all) of the topics covered by Memetic Computing are: Algorithmic Intelligence in Optimisation, Control and Design Hybrid (Parallel) Metaheuristics such as Tabu Search, Path relinking, Scatter Search, GRASP methods, Iterated Local Search, Simulated annealing, Variable Neighborhood Search, Evolutionary Algorithms, Learning Classifier Systems, Memetic Algorithms, Cultural Algorithms, etc. Approximate and exact algorithms for Combinatorial and Continuous Optimisation Integer and Linear Programming Ant Colony Computing Self-organisation, Self-Assembly, Self-Generation, Self-Healing of artificial systems Swarm Intelligence Neural networks Evolutionary Dynamics Memetic Theory Artificial Cultures in multi-agent systems, webbots and robots. Landscape Analysis Methodological aspects of experimental computing. Search based Software Engineering Genetic Programming Constraint Optimisation Representation and encoding studies Real-world applications Machine learning and Data Mining Multiobjective optimisation Artificial immune systems.
Keywords: Bioinformatics; Applied mathematics; Engineering mathematics; Statistical physics; Dynamical systems; Control engineering; Robotics; Mechatronics; Mathematical and Computational Engineering; Artificial Intelligence; Complex Systems; Control, Robotics, Mechatronics; Bioinformatics; Applications of Mathematics